Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content1. The role of business accelerators and incubators in supporting entrepreneurial projects in the entertainment sector and their impact on domestic tourism in the Kingdom  in light of the Covid-19 pandemicMrs. Jehan Abdullah Al-Shanbari , Mrs. Dareen Muhammad Bukhari , Mrs. Sanaa Fahm Al-Buqami , Dr. Dania Habibullah Qari Bey2. The Role of Applying Cybersecurity Standards on Organizational Excellence – A Field Study on Faculty Members at Taibah University in Madinah for the year 2022/ 2023 –Mrs. Rania Mohammad Sameer Da'as, Dr. Sabah Abdullah Al-Somali3. The mediating role of management information systems in the relationship between knowledge management and its impact on technology transfer Studying its application to managers and officials of information systems management at the Ministry of Education in the State of KuwaitMrs. Mariam Ghloum Ashkanani4. The degree of the application of knowledge management processes in "Al-Saeed University" and their impact on the excellence of institutional performanceMr. Mohammed Saif Mohamed Noman5. Impact of "Elktron Training" on the performance of employees at Safi DanonMr. Sameer Mohammed J. Alshehri6. The effect of corporate income tax on financial performance: evidence from PalestineDr. Salem Mohammad Abdelaziz Salem , Mr. Zaid Rebhi Hammad Qutait7. Indicators and Manifestations of the Balancing between International Carriage Parties  according to the Rotterdam RulesDr. Abdullah Yahya Mohammed Al-Houthi
Keywords: Journal of Economic, Administrative and Legal Sciences